The Human Cutaneous Chemokine System - Moser, Bernhard; McCully, Michelle L. (Frontiers in Immunology, 2011)
Irrespective of the immune status, the vast majority of all lymphocytes reside in peripheral tissues whereas those present in blood only amount to a small fraction of the total. It has been estimated that T cells in healthy human skin outnumber those present in blood by at least a factor of two. How lymphocytes within these two compartments relate to each other is not well understood. However, mounting evidence suggest that the study of T cell subsets present in peripheral blood does not reflect the function of their counterparts at peripheral sites. This is especially true under steady-state conditions whereby long-lived memory T cells in healthy tissues, notably those in epithelial tissues at body surfaces, are thought to fulfil a critical immune surveillance function by contributing to the first line of defence against a series of local threats, including microbes, tumours and toxins, and by participating in wound healing. The relative scarcity of information regarding peripheral T cells and the factors regulating their localization is primarily due to inherent difficulties in obtaining healthy tissue for the extraction and study of immune cells on a routine basis. This is most certainly true for humans. Here, we review our current understanding of T cell homing to human skin and discuss candidate chemokines that may account for the tissue selectivity in this process.